Vascular Endothelial Growth Factor Enhances the Expression of Urokinase Receptor in Human Endothelial Cells via Protein Kinase C Activation - Kroon, Marielle E.; Koolwijk, Pieter; Vermeer, Mario A.; van der Vecht, Bea; van Hinsbergh, Victor W. M. (Thrombosis and Haemostasis, 2001)
Among other proteolytic enzymes, the urokinase-type plasminogen activator (u-PA)/plasmin cascade contributes to cell migration and the formation of capillary-like structures in a fibrinous exudate. The u-PA receptor (u-PAR) focuses proteolytical activity on the cell surface of the endothelial cell and hereby accelerates the pericellular matrix degradation. Vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF)-2 enhance u-PA receptor expression in human endothelial cells. In this paper we show that the protein kinase C (PKC) inhibitors Ro31-8220 and GF109203X inhibit VEGF165-induced u-PAR antigen expression in human endothelial cells, whereas PKC inhibition had no effect on FGF-2-induced u-PAR antigen enhancement. In addition, inhibition of PKC activity had no effect on VEGF165-or FGF-2-induced proliferation in human endothelial cells. We conclude that VEGF165 induces u-PAR via a PKC-dependent pathway, whereas proliferation is induced via a different pathway probably involving tyrosine phosphorylation of proteins downstream of the VEGF receptors.
Keywords: u-PAR; VEGF; PKC; human endothelial cells